2009
DOI: 10.1161/circulationaha.108.808626
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological Effects of Late Percutaneous Coronary Intervention for Infarct-Related Coronary Artery Occlusion

Abstract: for the OAT-EP InvestigatorsBackground-The Occluded Artery Trial-Electrophysiological Mechanisms (OAT-EP) tested the hypothesis that opening a persistently occluded infarct-related artery by percutaneous coronary intervention and stenting (PCI) after the acute phase of myocardial infarction compared with optimal medical therapy alone reduces markers of vulnerability to ventricular arrhythmias. Methods and Results-Between April 2003 and December 2005, 300 patients with an occluded native infarct-related artery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
6
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 28 publications
(38 reference statements)
3
6
0
Order By: Relevance
“…67 There were no significant differences in heart rate variability, timedomain signal-averaged ECG, or T-wave variability parameters (all surrogate markers of ventricular instability) between either group at 30 days and 1 year after the AMI, which is consistent with the lack of clinical benefit from PCI in stable patients after AMI with persistently occluded infarct-related arteries in the main OAT study.…”
Section: Ventricular Arrhythmias After Myocardial Infarctionsupporting
confidence: 72%
“…67 There were no significant differences in heart rate variability, timedomain signal-averaged ECG, or T-wave variability parameters (all surrogate markers of ventricular instability) between either group at 30 days and 1 year after the AMI, which is consistent with the lack of clinical benefit from PCI in stable patients after AMI with persistently occluded infarct-related arteries in the main OAT study.…”
Section: Ventricular Arrhythmias After Myocardial Infarctionsupporting
confidence: 72%
“…67 There were no significant differences in heart rate variability, time-domain signal-averaged ECG, or T-wave variability parameters (all surrogate markers of ventricular instability) between either group at 30 days and 1 year after the AMI, which is consistent with the lack of clinical benefit from PCI in stable patients after AMI with persistently occluded infarct-related arteries in the main OAT study.…”
Section: Ventricular Arrhythmias and Sudden Cardiac Deathsupporting
confidence: 72%
“…Although previous studies showed an improvement in arrhythmic markers after late reperfusion of an infarct-related artery, 28,29 more recently, Rashba et al, 30 in a substudy of the OAT (Occluded Artery Trial), found no differences in heart rate variability between percutaneous coronary intervention with stenting of a persistently occluded infarct-related artery and medical treatment. However, this study included patients with subacute MI and a mean LVEF of 47% compared to an LVEF of 30% in the present study population with only 50% of the patients with chronic MI and 30% with Q waves in the CTO territory.…”
Section: Nombela-franco Et Al Vacto Primary Study 151mentioning
confidence: 93%